ANALISIS QOS WIRELESS LAN PADA PERANGKAT ACCESS POINT 802.11g - Purwanto, Timur Dali (JURNAL ILMIAH MATRIK, 2014)
Performance of wireless networks lies in the physical link and the most influential are the physical conditions such as distance, because the weaker the radio frequencies that can receive and make access to the network is slow, but the barrier of wall thickness (Fresnel Zone) and the adjacent signal interference (interference Co-Channel) of the other components could also lower the quality of the received signal enduser. Of problems occurred that may affect the overall performance of the network parameter AP is Qos (Quality of Service) such as delay, jitter, throughput, and packet loss. aims to determine the optimal wireless network performance to provide a good network quality of the physical aspects that guarantee a given Qos tailored to the applications used and the efficiency of the network Wireless LAN (Hotspot) at the University of Bina Darma for each enduser.